Biofeedback therapy in constipated, female patients and caused by radical hysterectomy or vaginal delivery. Issue 7 (20th June 2013) - Park, Soo‐Kyung; Myung, Seung‐Jae; Jung, Kee Wook; Chun, Yoon Hee; Yang, Dong‐Hoon; Seo, So‐Young; Ku, Hyun‐Sook; Yoon, In Ja; Kim, Kyung Jo; Ye, Byong Duk; Byeon, Jeong‐Sik; Jung, Hwoon‐Yong; et al.
Abstract Background and Aim Chronic constipation is frequently seen in women who have undergone hysterectomy or delivery. However, reports regarding anorectal physiologic features in those patients are rare. Patients with constipation associated with either radical hysterectomy or vaginal delivery were analyzed in order to clarify the anorectal physiologic features and the effectiveness of biofeedback therapy. Methods Of the constipated patients, a hysterectomy group (n = 40), delivery group (n = 41), and a control group (n = 89), who had no history of either surgery or delivery before developing functional constipation were included. Their anorectal physiological tests and the effectiveness of biofeedback therapy were investigated. Results The volume of desire to defecate was greater in the hysterectomy group than in the control group (86.5 ± 55.0 mL vs 62.9 ± 33.7 mL; P = 0.03), and more than 240 mL of maximal volume of toleration was more frequently noted in the hysterectomy group (32.5%) than in the delivery group (14.6%) and control group (13.5%) (P = 0.02).The failure of balloon expulsion was more frequently noted in the delivery group (44.0%) than in the hysterectomy group (15.0%) and control group (25.0%) (P = 0.01). The defecation satisfaction score was significantly increased after biofeedback therapy in the hysterectomy group (2.0 ± 2.7 vs 7.8 ± 1.5, P < 0.001), the delivery group (1.6 ± 2.1 vs 6.7 ± 2.0, P < 0.001), and the control group (2.5 ± 2.7 vs 6.9 ± 2.1, P < 0.001). Conclusions Rectal hyposensitivity could have been the characteristic mechanism in the hysterectomy group, whereas dyssynergic defecation could have been the cause in the delivery group. Biofeedback therapy was effective for both groups.